2015
DOI: 10.1016/j.media.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Trainable COSFIRE filters for vessel delineation with application to retinal images

Abstract: a b s t r a c tRetinal imaging provides a non-invasive opportunity for the diagnosis of several medical pathologies. The automatic segmentation of the vessel tree is an important pre-processing step which facilitates subsequent automatic processes that contribute to such diagnosis.We introduce a novel method for the automatic segmentation of vessel trees in retinal fundus images. We propose a filter that selectively responds to vessels and that we call B-COSFIRE with B standing for bar which is an abstraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
400
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 635 publications
(415 citation statements)
references
References 39 publications
2
400
0
Order By: Relevance
“…B-COSFIRE filters are trainable and in [6] they were configured to be selective for bar-like structures. Such a filter takes as input the response of a Difference-of-Gaussians (DoG) filter at certain positions with respect to the center of its area of support.…”
Section: B-cosfire Filtersmentioning
confidence: 99%
See 3 more Smart Citations
“…B-COSFIRE filters are trainable and in [6] they were configured to be selective for bar-like structures. Such a filter takes as input the response of a Difference-of-Gaussians (DoG) filter at certain positions with respect to the center of its area of support.…”
Section: B-cosfire Filtersmentioning
confidence: 99%
“…A model of the vessels based on their concavity and built by using a differentiable concavity measure was proposed in [18]. In previous works [6,35], we introduced trainable filters selective for vessels and vesselendings. We demonstrated that by combining their responses we could build an effective unsupervised delineation technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, identification and quantification of such changes are challenging tasks since the retina is extremely heterogeneous and, as a consequence low signal-to-noise ratio, nonuniform illumination and contrast shifts in the images complicate the automated detection and analysis of geometrical changes. The latest segmentation algorithms produce highly accurate vessel segmentations [4] [5] [6] [7]. Nevertheless, the identification of the mutually overlapping venous and arterial trees is a nontrivial problem.…”
Section: Introductionmentioning
confidence: 99%